"Two‐steps" seed‐derived plugs as an effective propagation method for the establishment of Miscanthus in saline–alkaline soil. Issue 6 (27th March 2021) - Zheng, Cheng; Xue, Shuai; Xiao, Liang; Iqbal, Yasir; Sun, Guorong; Duan, Meijuan; Yi, Zili
Abstract: Miscanthus, a perennial rhizomatous C4 grass, has emerged as a promising lignocellulosic crop. To avoid competition with food crops, marginal lands especially saline–alkaline soil are being recommended to grow Miscanthus across China. However, the challenges such as high cost and low reproduction coefficient associated with the propagation methods are impeding its large‐scale plantation in saline–alkaline soil. In this study, a "two‐steps" propagation method was designed, which was comprised of two phases: (1) seedling cultivation and (2) seedling strengthening. The parameters (substrate composition and plug size) for this method were determined. The optimal substrate composition of the seedling bed for M. sinensis, M. lutarioriparius, and their interspecific hybrids was peat and perlite at a ratio of 3:2, 3:1, and 3:3 by volume, respectively. The seedlings were transplanted into the plugs to deliver robust plantlets. The most appropriate plug size for M. sinensis, M. lutarioriparius, and their interspecific hybrids was 50 plugs (50 cm 3 /plug), 72 plugs (40 cm 3 /plug), and 72 plugs (40 cm 3 /plug), respectively. Three propagation methods, that is, direct sowing of seeds, rhizomes plantation, and "two‐steps" seed‐derived plugs for M. lutarioriparius were compared in saline–alkaline soil over 3 years (2014, 2015, and 2016). The establishment rate of the seeds directly planted was poor (zero). The performance (e.g., biomass yield) of the plants derived from the "two‐steps" seed‐derived plugs was better than that of the plants derived from rhizomes directly planted. Therefore, the "two‐steps" seed‐derived plugs can be regarded as an effective propagation method to upscale Miscanthus cultivation in saline–alkaline soil. Abstract : Saline–alkaline soil represents a vast area of marginal land that could be potentially utilized for biomass production. Miscanthus with rich natural variation and genetic diversity has ability to tolerate salt and alkali to a relatively high level. However, the challenges such as high cost and low reproduction coefficient associated with the propagation methods are impeding its large‐scale plantation in saline–alkaline soil. In this study, a "two‐steps" propagation method was designed to address the problem.